Implementasi Metode Pemberian Tugas dalam Meningkatkan Hasil Belajar IPA Materi Alat Pernapasan Pada Manusia - Haulussy, Momina; Smith, Alwi; Kapludin, Yusran (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2022)
The purpose of this study was to determine the improvement of science learning outcomes through the method of assigning assignments at the end of each meeting on human breathing apparatus material in grade V SD Inpres Lengkong, Salahutu District. This type of study is descriptive with a sample of 30 people taken using a population sample. The instruments used are tests, affective observation sheets, and psychomotor observation sheets. The data analysis used is descriptive data analysis of student learning outcomes, affective observations, and student psychomotor. The results of data analysis show that learning using assignments at the end of each meeting of breathing apparatus material in humans can improve student learning outcomes. This is shown by the increase in the average score of students, namely in the initial test of 53.33 and in the implementation of the final test where students follow the learning process using assignments at the end of each meeting the average score obtained classically is 73.11. Thus, it can be concluded that the learning process using assignments at the end of each meeting can improve student learning outcomes